Energy Cooperatives and Municipalities in Local Energy Governance Arrangements in Switzerland and Germany. (March 2020) - Schmid, Benjamin; Meister, Thomas; Klagge, Britta; Seidl, Irmi
Participation of citizens in local energy decisions is increasingly recognized as helpful for a successful decentralized energy transition. In this article, we focus on energy cooperatives in which private individuals jointly develop facilities to generate energy from renewable sources, thus involving citizens both politically and economically. Focusing on Switzerland and Germany, we show that there is a strong linkage between such cooperatives and municipalities, characterized by collaboration and support, and that the cooperatives are well suited as collaborating partners. We also show that federalist structures are most suited for such local arrangements as municipalities must have leeway to support cooperatives in a targeted manner and to compensate for shortcomings in the energy policy of superordinate governmental levels. Based on these results, we suggest that local governments should be given sufficient financial capacities and autonomy to strengthen implementation of a decentralized energy transition that involves citizens. However, we also recognize that municipal structures alone are often insufficient and that superordinate policies, especially national subsidies, remain essential. Hence, policies at the municipal and national levels should take greater account of citizen initiatives, such as energy cooperatives, which exhibit various noncommodifiable advantages relevant to the energy transition.